Geranyl Diphosphate Synthase (CrtE) Inhibition Using Alendronate Enhances Isoprene Production in Recombinant Synechococcus elongatus UTEX 2973: A Step towards Isoprene Biorefinery - Yadav I.; Rautela A.; Gangwar A.; Kesari V.; Padhi A.K.; Kumar S. (My University, 2025)
A hemiterpene, isoprene, is commercially produced from crude oil refining processes. As a result of fossil fuel depletion, isoprene production process development is gaining attention from recombinant cyanobacteria and other microbial systems for its industrial and biofuel applications. In the present study, a fast-growing and CO2-tolerant cyanobacteria, Synechococcus elongatus UTEX 2973, is engineered with Pueraria montana isoprene synthase (IspS) at neutral site I (NSI) in the genome of S. elongatus UTEX 2973. Furthermore, to enhance isoprene production a key enzyme (isopentenyl diphosphate isomerase, IDI) of the methyl-D-erythritol 4-phosphate (MEP) pathway is also overexpressed at neutral site III (NSIII). Wild-type and recombinant strains of S. elongatus UTEX 2973 (UTEX IspS and UTEX IspS.IDI) are studied for growth and isoprene production in the presence of an inducer (IPTG) and/or inhibitor (alendronate). Alendronate is used for the inhibition of geranyl diphosphate synthase (CrtE), downstream of the MEP pathway that catalyzes dimethylallyl diphosphate/isopentenyl pyrophosphate (DMAPP/IPP) condensation in the recombinant UTEX 2973 strains. The docking studies on SeCrtE (CrtE of Synechcoccus elongatus PCC 7942) and alendronate as an inhibitor have revealed that alendronate binds more tightly than IPP in the cavity of SeCrtE, with a higher number of intermolecular interactions and energy. The UTEX IspS strain has shown isoprene production below the limit of detection in the presence of an inducer and/or inhibitor; however, production studies using UTEX IspS.IDI showed a maximum production of 79.97 and 411.51 µg/g dry cell weight (DCW) in a single day in the presence of an inducer only and an inducer along with an inhibitor, respectively. The UTEX IspS.IDI strain produced 0.41 mg/g DCW of cumulative isoprene in the presence of an inducer and 1.92 mg/g DCW in the presence of an inducer as well as an inhibitor during six days of production. The yield improvement of isoprene is observed as being 4.7-fold by using the inhibition strategy, which is used for the first time in the recombinant cyanobacterial system. The average productivities of isoprene obtained from UTEX IspS.IDI are observed to be 2.8 μg/g DCW/h in the presence of an inducer and 13.35 μg/g DCW/h in the presence of an inducer as well as an inhibitor. This study provides a basis for the process development and yield improvement in isoprene production using a novel inhibition strategy in fast-growing recombinant cyanobacteria. Recombinant strains and metabolic pathway inhibition studies can be used in future attempts to photosynthetically produce hemiterpenes. © 2023 by the authors.